Modified Sawdust for Removal of Methyl Violet (Basic Dye) From Aqueous Solutions - HASHEMIAN, SAEEDEH (Asian Journal of Chemistry, 2010)
Sawdust an inexpensive material is currently being investigated as an adsorbent for removing undesired material from water. In this study, natural sawdust and modified ethylenediamine sawdust were used for sorption of methyl violet dye. The sorption characteristics of methyl violet by sorbent were studied under various experimental conditions. The effect of different parameters such as contact time, varying dye concentration, agitation time, pH of the medium and temperature was investigated. Simultaneous removal of methyl violet occurred at pH 10, contact time 1 h, 0.1 g of sorbent and room temperature (25 °C). Decreasing particle size increased the uptake of dyes. The kinetics of methyl violet dye sorption fitted a pseudo-second order rate expression. The equilibrium adsorption capacity of sawdust for methyl violet was obtained by using linear Freundlich and Langmuir isotherms.